The Use of Cohesive Device in Writing Cause and Effect Essay - Indah Wardaty Saud (ETERNAL (English Teaching Journal), 2015)
This study investigated the cohesive errors I composing essay writing done by undergraduate English Department students of University of Muhammadiyah Gorontalo, Indonesia. In elucidating the students’ difficulties in using cohesive devices, the researchers examined the cohesive errors both quantitatively and qualitatively. This study was analyzed based on an error analysis paradigm and Halliday and Hasan’s cohesion framework and taxonomy. The quantitative analysis investigated frequency and the percentage of cohesive errors and also the types of cohesive errors committed by the student. The qualitative analysis investigated linguistic a description and the explanation of the cohesive composed by the students.